Sex and Gender Differences in Rilpivirine based ART - Data from the HIVCENTER Frankfurt - Schüttfort, G.; Philipp, K.; de Leuw, P.; Herrmann, E.; Kann, G.; Khaykin, P.; Stephan, C.; Wolf, T.; Haberl, A. (Current HIV Research, 2019)
Objective: While Rilpivirine has shown high overall response rates in treatment-naïve patients without sex and gender specific differences in clinical trials, Sex and gender specific data in treatment experienced patients receiving rilpivirine are still limited. We conducted a 48 week efficacy and safety analysis in naïve and treatment experienced men and women using retrospective data from the HIVCENTER Frankfurt. Materials and Methods: In this retrospective observational study data of all patients who received a rilpivirine based regimen at the HIVCENTER between March 2011 and December 2015 were analyzed. Primary endpoint was the proportion of patients with any discontinuation until week 48. Virologic response rates (FDA snapshot analysis; HIV-1 RNA <50 copies/mL) were assessed at week 48. Results: 194 patients (34% female) were included in the analysis. 74% were treatment-experienced and 26% naïve, respectively. Discontinuations were observed in 31 (15.9%) patients. Regarding sex differences, the proportion of discontinuations was significantly higher in women than in men (24.2% vs. 11.7%; p=0.024; ODDS-Ratio = 2.41; CI 1.12 – 5.18). Virologic failure occurred in 8 PLWHIV (4.1%). Conclusion: While virologic overall response rates to rilpivirine based ART were high for both treatment-experienced and -naïve patients the proportion of discontinuations was significantly higher in women (24.2% vs. 11.7%; p = 0.024; ODDS-Ratio = 2.41; CI 1.12 – 5.18). Although the total number of patients with virologic failure was low (4.1%), the higher rate of ART discontinuations in female patients receiving RPV require close monitoring in the first months of treatment addressing special needs of women living with HIV.
Keywords: gender